Upaya Cyber Public Relations Dalam Meningkatkan Kegiatan Marketing PT Moladin Digital Indonesia - iin hardiyanti; Wirda Wirda (Jurnal Public Relations (J-PR), 2022)
AbstractPT Moladin Digital Indonesia is the first pioneer of an application that focuses on selling vehicles since 2019 and has been selling new or used cars online. PT Moladin Digital Indonesia belongs to the e-commerce category that only specializes in selling cars and motorcycles through applications. E-commerce is the process of buying or selling a product using electronic data via the internet. Seeing the trend in the use of social media and applications starting to have a very important role in the vehicle industry, the study aims to find out Cyber Public Relations in increasing PT Moladin Digital Indonesia's marketing activities. The concept used in this research is how to build engagement on social media proposed by Jefkins, namely Cyber Public Relations, Marketing Public Relations and New Media. The paradigm that will be used in this research is the constructivist paradigm using a qualitative descriptive approach. This research method is a case study. With the source of the data obtained from key informants are Mr. Arthur as Area Manager of Public Relations Moladin, then the supporting informant Mrs. Ita as sales manager. In collecting data, this study used participatory observation techniques, in-depth interviews, and documentation studies. The results of the discussion in this study indicate that the efforts that have been implemented in increasing PT Moladin Digital Indonesia's marketing activities in building trust and creating a positive image with the Moladin Care program are considered successful because it can be seen from the results of community achievements in using Moladin application services.Keywords: Cyber Public Relations, Marketing Public Relations, Social Media.